Lifetime use of psychedelics is associated with better mental health indicators during the COVID-19 pandemic - Cavanna, Federico Amadeo (2021)
Background and aimsThe COVID-19 pandemic and its consequences represent a major challenge to the mental health and well-being of the general population. Building on previous work on the potential long-term benefits of psychedelics, we hypothesized that lifetime use of these drugs could be linked to better mental health indicators in the context of the ongoing pandemic.MethodsTwo anonymous online surveys were conducted between April and June 2020, including questions about lifetime experience with psychedelics and other psychoactive drugs, and psychometric scales designed to measure personality traits, anxiety, negative, and positive affect, well-being, and resilience. Principal component analysis was applied to divide the sample into groups of subjects based on their drug use reports.ResultsFive thousand six hundred eighteen participants (29.15 ± 0.12 years, 71.97% female) completed both surveys and met the inclusion criteria, with 32.43% of the sample reporting at least one use of a psychedelic drug. Preliminary analyses showed that certain psychedelics were linked to improved mental health indicators, while other psychoactive drugs exhibited the opposite behavior. Lifetime psychedelic use was linked to increased openness and decreased conscientiousness, and to higher scores of positive affect. The reported number of past psychedelic experiences predicted higher scores of the secondary personality trait beta factor, which has been interpreted as a measure of plasticity. No significant associations between lifetime use of psychedelics and indicators of impaired mental health were observed.ConclusionWe did not find evidence of an association between lifetime use of psychedelics and poor mental health indicators. Conversely, experience with psychedelic drugs was linked to increased positive affect and to personality traits that favor resilience and stability in the light of the ongoing crisis.